Fuzzy - Angleberger, Tom; Dellinger, Paul, 1938- (Amulet Books, 2016)
Fuzzy, a robot, is the newest student at Vanguard Middle School. Part of the school's new Robot Integration Program, he is involved with a government project exploring artificial intelligence. Maxine Zelaster, a human, befriends Fuzzy, looking to teach him everything he will ever need to know about the good, the bad, and the ugly of middle school. What neither of them saw coming was BARBARA, a digital evaluation system whose mission to produce the perfect student could turn deadly.